Effective charge separation of inverted polymer solar cells using versatile MoS2 nanosheets as an electron transport layer - Lee, Kyu Seung; Park, Young Jae; Shim, Jaeho; Lee, Chil-Hyoung; Lim, Guh-Hwan; Kim, Hak Yong; Choi, Jin Woo; Lee, Chang-Lyoul; Jin, Yeonghoon; Yu, Kyoungsik; Chung, Hee-Suk; Angadi, Basavaraj; et al. (ROYAL SOC CHEMISTRY, 2019)
Molybdenum disulfide (MoS2) has been extensively used as a hole transport layer in many inverted polymer solar cell devices. However, its potential as an electron transport layer in a solar cell device has rarely been reported. In this paper, we demonstrate an iPSC with enhanced photovoltaic performance by the introduction of a MoS2 nanosheet (NS) interlayer. Herein, MoS2 NS thin films were uniformly deposited on a polyethylenimine ethoxylated polymer by an electrostatic interaction. The MoS2 NS interlayer in the iPSC device plays important roles as a sub-photo sensitizer and an electron transport layer and provides effective charge separation for the enhancement of device performance. iPSCs with MoS2 NSs based on bulk heterojunction active materials such as P3HT:PC60BM, PTB7:PC71BM and PTB7-Th:PC71BM showed maximum power conversion efficiencies of 3.54%, 8.12%, and 9.08%, respectively, which were 27%, 11%, and 15% higher than those of the reference, respectively. Furthermore, the enhanced photovoltaic performance and electron transport mechanism of the iPSCs with the MoS2 NSs were confirmed experimentally using finite-difference-time-domain modeling and time-correlated single photon counting (TCSPC) measurements. The computational simulation results showed that the light absorption of the iPSCs with the MoS2 NS interlayer was slightly better than that of the iPSCs without the MoS2 NS interlayer. The electron decay time of PTB7:PC71BM with the MoS2 NS interlayer at a wavelength of 700 nm was reduced to 60 ps from 100 ps of PTB7:PC71BM without the MoS2 NS interlayer. The efficient light absorption and electron transfer characteristics of MoS2 NSs significantly improved the photovoltaic conversion performance of the iPSC devices.
Keywords: MOLYBDENUM-DISULFIDE MOS2; THIN-FILM TRANSISTORS; MONOLAYER MOS2; PHOTOVOLTAIC PERFORMANCE; QUANTUM DOTS